Determination of Smart and Accurate Contest Participants at the Elementary School Level Using Profile Matching Method - Mirzon Daheri; Pandu Adi Cakranegara; Nurlailah; Gamar Al Haddar; Nurhadi (Jurnal Mantik, 2022)
Improving the quality of education for students is a key objective of school-based learning activities. A smart and accurate contest is one of the approaches and technology-based learning models utilized by teachers who actively cultivate the abilities and interests of their students. The school selects students who succeed in the academic field, as demonstrated by their results in each topic, then selects individuals based on the selection criteria and determines kids with the highest scores who are eligible to participate in the smart and accurate contest. The goal of this work is to present a decision-making model using the Profile Matching approach. Using the GAP comparison table, this method determines the GAP value between the ideal candidate and the candidate candidate. The research data shows that there are 5 alternative student candidates participating in the quiz competition and 4 assessment criteria, namely the Average Knowledge Aspect Value (C1), Skill Aspect Average Score (C2), Simulation Test Score (C3) and Test Runtime (C4). The assessment model employing the Profile Matching method was successfully applied to the problem of determining smart and accurate contest participants. The results indicated that there were three best alternatives for students participating in the smart and accurate contest: alternative A4 with a value of 4,7, followed by alternatives A1 and A2 with a value of 4,5.